AT‐101 downregulates BCL2 and MCL1 and potentiates the cytotoxic effects of lenalidomide and dexamethasone in preclinical models of multiple myeloma and Waldenström macroglobulinaemia. (17th November 2013) - Paulus, Aneel; Chitta, Kasyapa; Akhtar, Sharoon; Personett, David; Miller, Kena C.; Thompson, Kevin J.; Carr, Jennifer; Kumar, Shaji; Roy, Vivek; Ansell, Stephen M.; Mikhael, Joseph R.; Dispenzieri, Angela; et al.
Summary Multiple myeloma, the second most common haematological malignancy in the U.S., is currently incurable. Disruption of the intrinsic apoptotic pathway by BCL2 and MCL1 upregulation is observed in >80% of myeloma cases and is associated with an aggressive clinical course. Remarkably, there is no approved drug with the ability to target BCL2 or MCL1. Thus, we investigated the anti‐tumour effects of a pan‐BCL2 inhibitor, AT‐101, which has high binding specificity for BCL2 and MCL1 in preclinical models of plasma cell cancers (Multiple myeloma and Waldenström macroglobulinaemia). Gene expression and immunoblot analysis of six plasma cell cancer models showed upregulation of BCL2 family members. AT‐101 was able to downregulate BCL2 and MCL1 in all plasma cell cancer models and induced apoptotic cell death in a caspase‐dependent manner by altering mitochondrial membrane permeability. This cytotoxic effect and BCL2 downregulation were further potentiated when AT‐101 was combined with lenalidomide/dexamethasone (LDA). NanoString nCounter mRNA quantification and Ingenuity Pathways Analysis revealed differential changes in the CCNA2, FRZB, FYN, IRF1, PTPN11 genes in LDA‐treated cells. In summary, we describe for the first time the cellular and molecular events associated with the use of AT‐101 in combination with lenalidomide/dexamethasone in preclinical models of plasma cell malignancy.